Identification of Common Thalamocortical Dysconnectivity in Four Major Psychiatric Disorders. (1st December 2018) - Tu, Pei-Chi; Bai, Ya Mei; Li, Cheng-Ta; Chen, Mu-Hong; Lin, Wei-Chen; Chang, Wan-Chen; Su, Tung-Ping
Abstract: Background: Recent genetic and imaging analyses of large datasets suggested that common biological substrates exist across psychiatric diagnoses. Functional connectivity (FC) abnormalities of thalamocortical circuits were consistently found in patients with schizophrenia but have been less studied in other major psychiatric disorders. This study aimed to examine thalamocortical FC in 4 major psychiatric disorders to identify the common connectivity abnormalities across major psychiatric disorders. Methods: This study recruited 100 patients with schizophrenia, 100 patients with bipolar I disorder, 88 patients with bipolar II disorder, 100 patients with major depressive disorder, and 160 healthy controls (HCs). Each participant underwent resting functional magnetic resonance imaging. The thalamus was used to derive FC maps, and group comparisons were made between each patient group and HCs using an independent-sample t test. Conjunction analysis was used to identify the common thalamocortical abnormalities among these 4 psychiatric disorders. Results: The 4 groups of patients shared a similar pattern of thalamocortical dysconnectivity characterized by a decrease in thalamocortical FC with the dorsal anterior cingulate, anterior prefrontal cortex and inferior parietal cortex. The groups also showed an increase in FC with the postcentral gyrus, precentral gyrus, superior temporal cortex, and lateral occipital areas. Further network analysis demonstrated that the frontoparietal regions showing hypoconnectivity belonged to the salience network. Conclusion: Our findings provide FC evidence that supports the common network hypothesis by identifying common thalamocortical dysconnectivities across 4 major psychiatric disorders. The network analysis also supports the cardinal role of salience network abnormalities in major psychiatric disorders.